Tax Revenue Response to the Business Cycle - Sancak, Cemile (IMF Working Papers; Working Paper ;, 2010)
This paper examines tax revenue during the business cycle by estimating the relationship between tax revenue efficiency and the output gap. We find a positive and significant relationship between these variables; results are consistent for quarterly and annual data, and across advanced and developing economies. We also find that a worsening (improvement) in the VAT C-efficiency is driven by shifts in consumption patterns and changes in tax evasion during contractions (expansions). A key implication is that, particularly during major economic booms and downturns, policy makers should look beyond simple, long-run revenue elasticities and incorporate into their analysis the effects of the economic cycle on tax revenue efficiency.